Sistema de control del riesgo del lavado de activos y financiación del terrorismo para el mejoramiento del desempeño financiero de la organización Rafael Antonio Salamanca con nombre comercial Depósito de Drogas Boyacá - DDB - Cantor Galindo, Martha Inés; Tachy Vanesa, Ramos López (Universidad Antonio Nariño, 2024)
This research work arises with the purpose of generating a strategy to contribute to the mitigation of the financial risk detected in Depósito de Drogas Boyacá through the design of a system to control the risk of money laundering and terrorist financing through a proposal that contributes to the improvement of the financial performance of Depósito de Drogas Boyacá -DDB.